To expose or not to expose: the complexity of emotions in Pap smear acceptance - Baharom, Anisah; Paim, Laily; Abu Samah, Asnarulkhadi (IDOSI Publications, 2013)
The Pap smear test has been established as a screening method to detect cervical cancer at a precancerous stage. Yet, the coverage is still low in many developing countries. The paucity of studies which probe into the emotional barrier drove this study to explore further the role of emotions among women in their process of making decision to do the Pap smear test. This qualitative study employed interpretative phenomenological analysis from semi-structured in-depth interviews of nine women who had undergone the Pap smear test. The results revealed two main emotions: embarrassment and anxiety. The sub-themes for embarrassment are embedded value, imperfections, doubt trustworthiness, enormity of emotion, sex of health personnel matters and temporal and conditional significance. Whilst, the sub-themes for anxiety are what are they going to do to me and what are the consequences. These emotions stemmed from values and past experiences of these women. The barriers set by these emotions signify the importance of their role in preventing women from doing the Pap smear test. The enormity of these emotions calls for interventions to focus on assisting women to overcome them before they can accept to do the Pap smear test.